«The Instinct of Workmanship» in the Structure of Composer Activity. The Case of Ravel - Drach, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. It consists in considering the Ravel's music not only in the con- text of the author's artistic evolution, but also as but also as a unique example of composer's skill - an attribute of a true Master, whose creative process is subordinated to certain structural principles. The main objective of the study is to clarify the basic rational positions of Ravel's compo- sitional mastery, that modus operandi (the artist's usual way of solving creative problems) that defines him as an artistic individuality (which is understood as the integrity of the artist's artistic world). The methodology includes biographical (to clarify the circumstances of Ravel's life and ed- ucation), phenomenological (to study the composer's artistic individuality), and structural (to understand the main guidelines of creative activity). Abstracting from stylistic and genre premises, let us try to understand what place skill occupies in the structure of composer's activity, which unites motivating motives, guidelines, actions and goals. This general structure is made specifically artistic by two additional parameters: the measure of talent and one of its components - the "instinct of workmanshipl (so-called Т. Veblen term).Results and conclusions. Like any human activity, composer practice is a special type of communication. Its unity is ensured by a structure that includes “motives, certain guidelines, actions, and goals.”It is made specifically artistic by additional parameters: the measure of talent and the “instinct of mastery,”(оr “the instinct of workmanship” by T.Veblen), which sets the intensity of using the primary resource of talent and regulates the vectors of its training, development, and existence. Ravel's music is a model of composer's skill. The report clarifies the basic options of his composer's skill, his “the instinct of workmanship”, that modus operandi (the artist's usual way of performing certain creative tasks, which determines the integrity of his artistic world). During his formative years, D'Annunzio's "bella figura" was important, among other things. Through the prism of D'Annunzio, Ravel reads the epigrams of Clément Marot. The Renaissance poetics of the style marotigue, strangely rhyming with the eclecticism of decadence, passing through the filters of the composer's good taste and dandyism, leaves behind the habit of distancing himself from the objects of reproduction. This guideline becomes the cornerstone of Ravel's compositional mastery. The second operating option involves reproducing one's Presence in the text as a deviation from the “zero degree of writing.” Ravel tested, varied, and maximized his authorial “degree of displacement” in his compositional writing on his way to the late style dépouillé.(this is clearly visible in his polyphonic technique of competition and original fugues, and the Piano Trio). The third option of Ravel's mastery is a special mechanism of catharsis. Ravel, like M. Proust, understood well that ideas, including musical ones, are "produced" by suffering, and the transformation of suffering into an idea causes a feeling of pleasure, including through the awareness of the skill with which this transition was made.